2012 IEEE/RSJ International Conference on Intelligent Robots and Systems 2012
DOI: 10.1109/iros.2012.6386061
|View full text |Cite
|
Sign up to set email alerts
|

Local randomization in neighbor selection improves PRM roadmap quality

Abstract: Abstract-Probabilistic Roadmap Methods (PRMs) are one of the most used classes of motion planning methods. These sampling-based methods generate robot configurations (nodes) and then connect them to form a graph (roadmap) containing representative feasible pathways. A key step in PRM roadmap construction involves identifying a set of candidate neighbors for each node. Traditionally, these candidates are chosen to be the k-closest nodes based on a given distance metric. In this paper, we propose a new neighbor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…In particular, it is shown that a nearly random tree search can perform virtually identically to the well-known RRT algorithm and that removing the workspace decomposition from XXL yields a (nearly) random graph that can perform well in certain instances of planning for R2 and planar kinematic chains. The benefits of randomizing the neighbor selection have been demonstrated previously for the PRM (McMahon et al, 2012), showing that connecting to a random subset of the k -nearest neighbors can result in better connected roadmaps in a variety of planning queries with rigid and articulated systems.…”
Section: Discussion: Guiding Heuristics In High-dof Sampling-based mentioning
confidence: 72%
“…In particular, it is shown that a nearly random tree search can perform virtually identically to the well-known RRT algorithm and that removing the workspace decomposition from XXL yields a (nearly) random graph that can perform well in certain instances of planning for R2 and planar kinematic chains. The benefits of randomizing the neighbor selection have been demonstrated previously for the PRM (McMahon et al, 2012), showing that connecting to a random subset of the k -nearest neighbors can result in better connected roadmaps in a variety of planning queries with rigid and articulated systems.…”
Section: Discussion: Guiding Heuristics In High-dof Sampling-based mentioning
confidence: 72%
“…Connecting all possible pairs of samples is computationally unfeasible, and it has been shown that only connecting the k-closest neighbors results in a roadmap of comparable quality [26].…”
Section: Connectionmentioning
confidence: 99%
“…This may not be the case if the edges are not unique, a condition which may occur if V is low and k or k is high. Typically, k is a constant and is normally very low compared to V [3], [9], so our assumption is emperically valid. Also, selecting unique random neighbors increases the possibility that the resulting edge connection is unique.…”
Section: A Number Of Edgesmentioning
confidence: 99%
“…While selecting closest neighbors is the defacto standard in motion planning algorithms, it is not uncommon to explore random neighbor selection [1], [12], [13]. In fact, some studies have shown that random neighbor selection does improve roadmap quality [9].…”
Section: A Number Of Edgesmentioning
confidence: 99%